KRITIK TEORI MASYARAKAT SAKRAL DAN MASYARAKAT PROFAN: Relevansi Pemikiran Sosial Durkheim dalam Wacana Penegakan Syariah di Indonesia Criticism Of The Theory Of The Sacred And Profane Society: Relevance of Durkheim’s Sociological Thought in Discourse of Sharia Enforcement of in Indonesia - Mibtadin Mibtadin (Balai Penelitian dan Pengembangan Agama Semarang, 2016)
Durkheim’s Social Theory looks societies as the sacred. He argues that in each society, there is a general system of belief which legitimatizes a social order that lead to collective awareness, network, binding symbol. These keep the social order continuously. Religions bring meanings to individual and social life, as well as give hope for external life in the hereafter. Religion takes a part in strengthening the social group’s norms, moral sanctions to individual behavior, and shared objective foundations of values for the society. This is a library research which tries to explain the relevance of Durkheim’s social theory on the recent modern Indonesian context that is more open, pro-alteration, religious plurality, and tend to take side on the certain group. Findings of this study portray that Society had experienced the paradigm shifting from sacred society to profane society, such as there is an idea of enforcing Islamic law in Indonesia. Durkheim’s sociological theory is considered less able to explain the phenomena of religious pluralism, especially on the case of suicide bombing in the name of religion (jihad). Secondly, religion is used to commit violence and to claim their rightness.